The battle against rural poverty and other challenges of development: Empirical analysis of women empowerment programme of Justice, Development and Peace Movement (JDPM) in Osun State, Nigeria - Helen Faborode; Titus Olugbenga Alao (Acta Agronómica)
The vital role played by women in agriculture and non-farm activities for achieving food security and economic growth led to the recognition of women as a vital instrument by both government and non-governmental organizations in the ‘battle’ against rural poverty and other challenges of development process. Hence, this article analysed the women empowerment programme of Justice, Development and Peace Movement (JDPM) of Osogbo Catholic Diocese in Osun State with a view to enhancing its effectiveness. The impact of the programme on the beneficiaries was assessed on four randomly selected communities from each of the three administrative zones of Osogbo, Ila and Ilesa. Twenty-five percent of the participants were proportionately sampled from each community selected, making 104 respondents. Structured interview schedule was performed for each data collection from programme beneficiaries while seven key informants were interviewed among the workers of the Diocese. Descriptive statistics (frequency counts, mean, percentages and standard deviation) and Pearson correlation was used to make inferences. Some of the results revealed that members of all religions practiced in the area benefitted from the programme. Results also revealed that age (r= -0.514), group size (r= -0.448), years of schooling (r=0.407) were significantly related to achievement of programme objectives at 0.01 level of significance while number of community associations (r=0.201), size of enterprise (r=0.448), and income (r=0.205) had significant relationship at 0.05 level of significance. The study also revealed that the programme had made the beneficiaries self reliant through skill acquisition but faced with financial constraint to start or expand the businesses learnt. It was recommended that the beneficiaries should be linked with financial institutions or banks where they could access loan with ease.